ADAPTASI MASYARAKAT TERHADAP BENCANA LONGSOR LAHAN BERDASARKAN TINGKAT KERAWANAN DI KECAMATAN BANYUMANIK KOTA SEMARANG - Utami, Otty Damayanti; Tjahjono, Heri; Sriyono, Sriyono (Geo-Image, 2017)
This study aims to identify the distribution of vulnerable areas of landslide and assess the society adaptation towards landslides in Banyumanik Distric, Semarang. The population in this study whole units of the terrain and the people in the Banyumanik Distric. Sampling in this study use sampling area on 19 terrain units and 80 respondents who are determined using Dixon B. Leach. This study uses a scoring method for mapping vulnerable areas of landslide and descriptive percentage to determine the level of societyâs adaptation to landslides. The results of the study explains that level of vulnerability index in Banyumanik District. The high level of landslide is 842,13 Hectares (27,23 %), intermediatte level is 308,66 hectares (9,98%), the low level is 1,058 hectares (34,21%), and the most low level is 883,80 Hectares (28,58%). The society conduct landslides adaptation according to their knowledge and experience. The classifier of society adaptation to landslides including three aspects: physical, economic, and social aspects.